Hubungan Tingkat Stres dengan Gangguan Siklus Menstruasi pada Remaja Putri - Nunung Nurhayati; Nanik Yuliwati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Every woman's menstrual cycle is not always normal, many women experience menstrual cycle disorders such as oligomenorrhea, polymenorrhea and amenorrhoea. Stress is a factor that can affect menstrual cycle disorders, such as menstrual cycle disorders in young women. To determine the relationship between stress levels and menstrual cycle disorders in young women at SMPN 2 Majalaya Karawang. This research method used an analytic survey research with a cross-sectional design. The population in the study amounted to 217 class IX teenage girls. The samples taken were 69 respondents using the proportionate stratified random sampling method. Instruments in the form of a questionnaire Perceived Stress Scale (PSS-10) and instruments measuring menstrual cycle disorders. Data analysis used descriptive analysis (univariate) and bivariate. The research results show that there is a relationship between stress levels and menstrual cycle disorders in young women at SMPN 2 Majalaya Karawang. It is recommended that the school provide counseling to young women about reproductive health, especially about menstruation. Then to provide space for counseling or discussion about solving problems that are being faced by young women, so that they can handle and reduce stress on young women.